Managing Organizational Crisis and Brand Trauma - Tafoya, Dennis W. (Springer International Publishing, 2018)
This book offers a framework for dealing with a new phenomenon affecting organizations and their stakeholders: brand trauma. Brand trauma puts an organization's credibility at risk as stakeholders, shaken by the effects of a crisis or a crisis' poor management reassess their relationship with the organization. The Deepwater Horizon oil spill, police harassment, Volkswagen's tampering with pollution devices, Wells Fargo's treatment of customer accounts, and the sexual exploits of politicians, educators and other high profile individuals are organizational crises that may trigger brand trauma. The author discusses both organizational and brand trauma with models and illustrations. Those in journalism, law and the justice department, criminologists, marketing, and public relations specialists well as members of an organization's leadership teams and advisory boards will find the material useful. .